Troubling Survivorism in The Bluest Eye. (29th April 2019) - Ropp, Sarah
Abstract: This essay takes as its central concern the binary opposition between survival and victimization in order to problematize the very notion of survival as it has been constructed ideologically in the highly individualistic culture of the United States; that is, as the positive assertion of personal agency that allows one to overcome the passivity associated with victimhood. Drawing from Marilyn Nissim-Sabat's theorization of the victim-survivor binary and Elias Canetti's definition of the survivor, I propose "survivorism" as an ideology centered around claiming the identity of survivor through the denial of one's own vulnerability. I discuss Toni Morrison's The Bluest Eye (1970) as a novel that, despite Morrison's hopes for it, participates in two of survivorism's most destructive aspects, as I identify them: the reliance on a sacrificial victim in order to assert one's survival and the inevitability of victim-blaming in order to believe in the myth of "deserved" suffering. Engaging with my own position as a raced, classed reader, I argue that white readers are particularly susceptible to reading the novel in this way due to the way it appears to confirm long-held suspicions about the failures of the black family to overcome structural oppression through force of individual will. Ultimately, I suggest, there is a way to read The Bluest Eye that takes full advantage of the text's potential to trouble the troubling survivorism it seems, on first reading, to support.